(untitled) (INNOVATIVE ECONOMY, 2026)
Marchenko T.V. ECONOMIC NATIONALISM AS A COMPONENT OF UKRAINE’S INTERNATIONAL RELATIONS Purpose. The aim of the article is to provide a theoretical substantiation of economic nationalism as a component of Ukraine’s international economic relations and to determine its role under conditions of war and post-war economic transformation. Methodology of research. A complex of general scientific and special methods were used to achieve the set goal, including systemic, structural and functional, comparative, and analytical approaches. The systemic method made it possible to consider economic nationalism as an integral element of international economic relations. The structural and functional method was used to identify the key instruments of its implementation in foreign economic policy. The comparative method allowed for the revealing of the transformation of economic nationalism under globalization and European integration. The analytical method was applied to generalize Ukraine’s current economic policy practices under wartime conditions. Findings. The essence of economic nationalism as an instrument of “managed integration” in the system of international economic relations is determined. The main tools of its implementation, including trade, investment, and industrial policies, as well as participation in global value chains, are analysed. The study examines Ukraine’s current practice, particularly the reorientation of its foreign economic relations, the growing role of the European Union, and support for strategic sectors under wartime conditions. The key constraints related to international obligations and institutional challenges are identified. Originality. For the first time, economic nationalism has been substantiated as a component of Ukraine’s international economic relations under conditions of war and global transformations, which, unlike existing approaches, makes it possible to consider it as a comprehensive instrument for combining integration processes with the protection of national economic interests; the approaches to defining the role of economic nationalism as a tool for ensuring a balance between economic openness and the need to preserve economic sovereignty have been improved; further development has been given to the theoretical substantiation of the “managed integration” model as a modern form of implementation of economic nationalism. Practical value. The obtained results can be used in the development of Ukraine’s state economic and foreign economic policies, in the formulation of post-war recovery strategies, and in the teaching of courses on international economics and international relations. Key words: economic nationalism, international economic relations, foreign economic policy, integration, economic resilience, strategic sectors.